2009
DOI: 10.1007/s00421-009-1055-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of training status on the drop in muscle strength after acute exercise

Abstract: Skeletal muscles fatigue after exercise, and reductions in maximal force appear. A difference in training status between the legs was introduced by unilateral immobilization of the calf muscles for 2 weeks in young men, who were randomly assigned to two groups, either a RUN group (n = 8) that was exposed to prolonged exercise (1-h running: individual pace) or a REST group (n = 12) that did no exercise after immobilization. Cross-sectional area (CSA) of the triceps-surae muscles was calculated by magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(57 reference statements)
0
5
1
Order By: Relevance
“…Contrary to the changes in muscle mass reported previously [28], we found no significant modulation of total or phosphoprotein levels of Akt, GSK3β, 4EBP1, ubiquitin or MURF1 in Study 2 (Figure 3B). Total and phosphorylated levels of mTOR and S6k were below the detection threshold.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the changes in muscle mass reported previously [28], we found no significant modulation of total or phosphoprotein levels of Akt, GSK3β, 4EBP1, ubiquitin or MURF1 in Study 2 (Figure 3B). Total and phosphorylated levels of mTOR and S6k were below the detection threshold.…”
Section: Resultscontrasting
confidence: 99%
“…Muscle strength was measured after 2 (REHAB 2 W) and 6 (REHAB (6 W) weeks of rehabilitation and muscle CSA was measured at the REHAB (6 W) time point as well. Muscle strength and size data from the PRE and IMMO time points in this study have been reported elsewhere [28]. Muscle strength and size were measured as described previously [28,29] Briefly, strength was maximal voluntary (isometric) plantarflexion strength with extended knee exerted against a plate connected to a strain gauge, while muscle CSA was measured from MR slice scans 10 cm distal to the caput fibula.…”
Section: Methodsmentioning
confidence: 99%
“…Reductions in spontaneous activity due to asthenia have been reported to occur after acute ESs, especially after the resistance to activity in untrained volunteers, which may indicate the need for caution when prescribing this type of activity to elderly subjects. 38,39 In conclusion, a single session of aerobic exercise with walking was effective for immediate and late BP reductions in elderly volunteers. The use of activity monitors to determine the actual periods of sleep was more effective for detecting reductions in BP during sleep than the fixed-time method.…”
Section: Discussionmentioning
confidence: 88%
“…Reduction in maximal force and skeletal muscle fatigue after 1 hour of running was 41% in the immobilized leg (for 2 weeks) and 10% in the other leg of young nonathletes. 19 Interesting findings have been discovered when studying changes in strength measurements on a weekly basis. The ES did not change significantly only in the fifth and the tenth week.…”
Section: Discussionmentioning
confidence: 99%